Inovasi Pendidikan Bahasa Indonesia: Pendekatan Teknologi dan Pembelajaran Berbasis Keterampilan - Yoga Saputra Manihuruk; Rizki Sitanggang; Gabrella Anastasya Ginting; Putri Raihan Lubis; Ano Victory Sinaga; Fitriani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The skills-based learning approach is a learning approach that is directed so that students can develop the life skills needed to maintain survival and develop themselves. This research aims to examine and describe Indonesian language education innovations using a technology approach and skills-based learning, by identifying the benefits, impacts and challenges faced in its implementation. The research method in this writing uses a type of research in the form of literature study. Results and discussion of this research There are several benefits, impacts and challenges in its implementation, which require support and cooperation from all parties involved in Indonesian language education, as well as improving facilities, literacy, readiness, discipline, responsibility, ethics, skills, competence, and professionalism of teachers and students.